KINERJA PT. PLN (PERSERO) DALAM MENANGGAPI KELUHAN PELANGGAN DI KOTA SORONG PROVINSI PAPUA BARAT - KAMINISUBUN, CELINE; TULUSAN, FEMMY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The purpose of this study is to determine how the performance of PT PLN in the complaint/ complaintsin the city of sorong, west papua province.This research use method approach of descriptive –qualitative. based on the theoreatical study, the performanceview from the three dimensions of organizational performance the public service namely productivity,responsiveness and accountability. The research informansin the capture of elemen of the of the official/employeePLN the city of sorong as many as 4 people, and community customers of PLN as much as 4 people. Data collectionusing interview guidelines ,while the analysis technique used is the analysis of the interactive model of Miles andhubernann.Based on the results of data analysis on apple conclusion (1) the productivity has been quite good in view of theimplementation of the set, ability carry out the service, the level of achievement, the realization of the operatingbudget, the efficiency of use of facilities/ infrastructure work, and optimilisasi utilization of potensial HUMANresources officer. (2) responsiveness has been quite good in view of programs and actions to respond to customercomplaints, but still less good in view of speed and punctuality (3) accountability is good enough in view of theopenness of the give an answer to the community/ customer about the program as well as customer satisfaction.Starting from the results of the study then can in kemukan some advice : (1) team technical services in the needto consider in more into four tim/ group to four wilayah/ a different location. (2) the service to responded withrapid and timely complaints customers hendaklah in increase and in sesuaikan with the needs of customers. (3)accountability hendaklah more transparent to utilize in optimally media the and social media that thereKey Word : The Performance, Customer Service PLN